X-ray and neutron scattering of multiferroic LuFe2O4 - Lawrence, Shane Michael (Curtin University, 2011)
Multiferroic materials have recently begun to attract significant scientific interest due to their potential applications in the design of modern electronic devices. Currently, the magnetic properties of materials form the basis of our electronic data storage and have the potential to enhance the logic operations performed in electronic devices (such as computers and sensors). Non-volatile magnetic memory is used in data storage devices, such as the hard drives found in personal computers, where data is encoded via the magnetisation state of magnetic domains in the device with one of two states: either up or down (M ↑ or M ↓); the state is determined or changed by interacting with the magnetic flux about the domain. Furthermore, in current computing and sensor technology, logic operations are performed with arrays of transistors; however, in spintronics ("spin transport electronics") the electric current itself is spin polarised and there is data encoded in the current itself. Circuit elements in such a system are magnetic devices that interact with the electron spin.Magnetoelectric multiferroics are materials that have both a spontaneous ferroelectric polarisation (P) and magnetic magnetisation (M). Polarisation may be manipulated by an electric field and magnetisation by a magnetic field, hence the potential of multiferroics lies in the coupling between the two degrees of freedom and the manipulation of magnetisation by an applied electric field and vice versa. The properties of a magnetic device could be altered "on-the-fly" by applying an electric pulse, and in the context of the examples provided this would greatly diversify the logic elements in spintronic circuits. Furthermore, with both polarisation and magnetisation a multiferroic domain can take on one of four states (M ↑ P ↑, M ↑ P ↓, M ↓ P ↑, or M ↓ P ↓) dramatically increasing data storage density over the current binary system.Lutetium ferrite (LuFe2O4) is a multiferroic material in which both the magnetisation and polarisation arise from the iron sites and with strong iron-iron correlations the material is a promising candidate as a high temperature multiferroic. The material has a layered structure with bilayers of FeO separated by single layers of LuO on a hexagonal lattice. Frustrated 2D charge order exists below 550 K which transitions to 3D charge order below 330 K and simultaneously frustrated ferrimagnetic order exists in the multiferroic phase below 250 K. X-ray and neutron scattering experiments have been performed in order to characterise the ferroelectric and ferrimagnetic order and magnetoelectric coupling in this material.Resonant x-ray scattering (RXS) was performed on the Material Science beamline of the Swiss Light Source where the energy dependence of the superlattice reflections corresponding to the charge order was collected. Non-linear regression using a custom Levenberg-Marquadt algorithm was applied in order to extract the anomalous scattering factors which demonstrated the superlattice reflections were described by a charge order model. Furthermore, the chemical shift was shown to correspond to full Fe2+/Fe3+ charge disproportionation. The absence of any polarisation or azimuthal dependence, shown by resonant x-ray scattering data collected on the ID20 beamline of the European Synchrotron Radiation Facility, confirmed the prediction of Nagano et al. that the orbital moments of the Fe2+-sites exist in a disordered glassy state.X-ray absorption near edge structure (XANES) calculations were performed using the FDMNES program in order to assess the validity of the anomalous scattering factors obtained in the RXS experiment and to further test the charge order model. It was shown that the characteristic features of the experimentally determined functions can be qualitatively reproduced by calculations using the known charge order model. Furthermore, these functions were shown to reproduce the phase of the RXS data further demonstrating that the reflections result from a pure charge ordered phase.Inelastic neutron scattering performed on the PUMA triple axis spectrometer of the FRMII demonstrated that magnetic critical scattering is observed at 250 K. A broad peak in the temperature dependence is observed rather than the characteristic divergence of a magnetic transition: this is attributed to broadening of the transition by the distribution of oxygen stoichiometry in the sample and ferroelectric fluctuations integrated into the data due to poor c-axis resolution. Pyroelectric current and magnetometry measurements demonstrate a peak in the magnetic susceptibility and a step in the polarisation at approximately 215 K, well below the magnetic transition. Elastic neutron scattering experiments performed on the E2 flat cone diffractometer of the Helmholtz-Zentrum Berlin demonstrate these features correspond to a 2D-to-3D magnetic transition that has previously only been predicted by anomalies in other measurements.An applied field study performed by neutron scattering on the E2 flat cone diffractometer of the Helmholtz-Zentrum Berlin and x-ray scattering on the PX1 protein crystallography beamline of the Australian synchrotron demonstrate the control of the magnetic domain population with an electric field, contrary to other recent reports on this topic. Furthermore, the observed magnetoelectric coupling is inconsistent with current models of the magnetic structure of this system. The x-ray measurements demonstrate a disorder-to-order effect by the applied electric field as 3D order is preferred with an increase in the intensity of all satellites.Temperature dependent x-ray powder diffraction data collected on the Powder Diffraction (PD) beamline of the Australian Synchrotron has demonstrated anisotropic thermal expansion with negative thermal expansion of the c-axis in this material. Electron density mapping by Fourier analysis shows the disorder of the oxygen between the electrically static Lu ions and the neighbouring Fe ions, as electron hopping between Fe2+ and Fe3+ leading to a corresponding variation on the Fe-O bond length. Reversible structural distortions are observed indicating a piezoelectric effect in this material caused by the crushing during sample preparation. Furthermore, weak reflections in the x-ray patterns, corresponding to a monoclinic sublattice, suggest a monoclinic distortion of the oxygen sites which is supported by neutron powder diffraction collected on the ECHIDNA instrument of the OPAL reactor.